Ответ:
Пошаговое объяснение:
1) 3х+у=6
6х-у=3
Решение
Из первого: у=6-3х
Вставляем во второе
6х-(6-3х)=3
6х-6+3х=3
9х=3+6
х=9:9
Находим у:
у=6-3х
у=6-3*1
у=3
Проверяем
3*1+3=6 верно
6*1-3=3 верно
2) Аналогично
3х+у=8
2х-у=2
Из первого
у=8-3х
2х-(8-3х)=2
2х-8+3х=2
5х=2+8
х=2
у=8-3*2
у=2
3*2+2=8 верно
2*2-2=2 верно
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) 3х+у=6
6х-у=3
Решение
Из первого: у=6-3х
Вставляем во второе
6х-(6-3х)=3
6х-6+3х=3
9х=3+6
х=9:9
Находим у:
у=6-3х
у=6-3*1
у=3
Проверяем
3*1+3=6 верно
6*1-3=3 верно
2) Аналогично
3х+у=8
2х-у=2
Из первого
у=8-3х
Вставляем во второе
2х-(8-3х)=2
2х-8+3х=2
5х=2+8
х=2
у=8-3*2
у=2
Проверяем
3*2+2=8 верно
2*2-2=2 верно